Poverty and Social Impact Analysis (PSIA) : Reviewing the Link with In-Country Policy and Planning Processes - Synthesis Report - World Bank (World Bank, 2012)
The synthesis report concerns to go beyond a summary of the country studies to provide lessons and recommendations on how to further improve Poverty and Social Impact Analysis (PSIA) effectiveness. To do so, it draws on findings from country case studies, the literature and recent internal Bank reviews (World Bank 2006, 2008) on PSIA. The synthesis is structured in three parts. Section two reviews the role of PSIA in country work drawing on internal guidance from the Bank and the wider literature. It introduces the PSIA framework and the main elements of an effective PSIA. Section two ends with a presentation of the review framework and the approach to sampling and methodology for the country studies. Section three presents the bulk of the review findings and lessons learned with a focus on lessons for embedding PSIA into country processes. Section four addresses the future of PSIA with recommendations aimed at: (i) improving the influence that PSIA has on policy and planning processes in-country, and (ii) ensuring that it is applied more routinely by partner governments and Bank programs.